ADS652 : Public finance / Faculty of Administrative Science & Policy Studies - UiTM, Faculty of Administrative Science & Policy Studies (2023)
The course gives an indepth understanding of the components of public finance. The various government financial activities which include taxes administration, public debt, procurement, accounting and auditing and their effects of the on the economy will be examined.The course will also emphasis on the issues of control of funds, accountability, transparency and integrity in public financial management. .